2015
DOI: 10.1007/s11235-015-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Accurately and quickly calculating the weighted spectral distribution

Abstract: The weighted spectral distribution (WSD) is a measure defined on the normalized Laplacian spectrum. It can be used for comparing complex networks with different sizes (number of nodes) and provides a sensitive discrimination of the structural robustness of complex networks. In this paper, we design an algorithm for the accurate calculation of the WSD in large-scale complex networks by utilizing characteristics of the graph structure. As an extension to Sylvester's Law of Inertia for the calculation of the WSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This paper chooses spectral property = ∑ (1 − ) ‖ ‖ to describe the distance, where ( = 1,2, ⋯ , ‖ ‖) are all the eigenvalues of the normalized Laplacian matrix of graph [34] because our recent work has demonstrated that the spectral property is a good indicator of the average path length [26]. However, the former can be calculated faster using the circle enumeration method than the latter [28].…”
Section: A Global Statistical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper chooses spectral property = ∑ (1 − ) ‖ ‖ to describe the distance, where ( = 1,2, ⋯ , ‖ ‖) are all the eigenvalues of the normalized Laplacian matrix of graph [34] because our recent work has demonstrated that the spectral property is a good indicator of the average path length [26]. However, the former can be calculated faster using the circle enumeration method than the latter [28].…”
Section: A Global Statistical Propertiesmentioning
confidence: 99%
“…Recently, we have partitioned the Internet transit and stub AS nodes into seven categories by analyzing the physical mean of the normalized Laplacian spectral properties [24][25][26][27][28][29]. However, these works only provided a static node classification and have not yet structurally distinguished the core from the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] In general, the sum over the 4cycles represents the quasi-randomness of the graph in a nonregular case. [22,23] Therefore, four is considered to be the suitable value of the parameter N. [4][5][6]…”
Section: Wsdmentioning
confidence: 99%
“…[2] Moreover, Wu et al [3] rigorously demonstrated that the feature is asymptotically independent of the order of regular graphs in which each node has an identical expected degree. However, our recent work [4,5] found numerically that the stability of the natural connectivity does not work in scale-free networks. The WSD is another spectral graph feature defined on the normalized Laplacian spectrum that strongly corresponds to the distribution of random N-cycles in a network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation